BIOECOLOGY OF LOKAN CALM (Geloina erosa) IN THE MANGROVE ECOSYSTEM OF BURUK BAKUL VILLAGE, BUKIT BATU DISTRICT, BENGKALIS REGENCY, RIAU PROVINCE - Purba, Marantha Merari; Fajri, Nur El; Yuliati, Yuliati (Politeknik Kelautan dan Perikanan Dumai, 2025)
Mangrove ecosystems are characterized by the high diversity of associated biota found, such as sea scallops. Sea scallops are filter feeders and suspension feeders that live at the bottom of the waters by burying themselves in sediment. This study aims to determine the biological aspects of sea scallops (morphometrics, density, distribution, and growth) and ecological aspects (mangrove vegetation structure and knowing the condition of sediment fractions and organic matter) in Buruk Bakul Village, Bukit Batu District, Bengkalis Regency, Riau Province. Sampling was carried out on transects containing 9 plots measuring 1 x 1 m² with a depth of 30 cm and a distance between transects of 100 m. Sampling and observation were carried out 3 times with an interval of 2 weeks. The results showed that the morphometric size of sea scallops varied. The density value of lokan clams ranges from 150 ind/ha to 2,700 ind/ha, with the highest lokan density at station I, natural mangrove forest conditions, and no community activities. The distribution pattern of lokan clams is categorized as uniform with an average value of <1. The growth pattern of lokan clams shows a negative allometric pattern, namely b <3. The highest density of mangrove vegetation is at station I, with 1,522 trees/ha, in a good category. The highest sediment fraction is the mud fraction, ranging from 30.24% to 84.6%. The highest organic matter content is at station I with a value of 28.37%. The results of the study showed that the density, growth, and morphometrics of lokan clams in Buruk Bakul Village were significantly influenced by the ecological conditions of the mangrove forest, especially the density of mangrove vegetation, substrate composition, and concentration of organic matter in the sediment.